Performance of Al2O3-SiO2/PAG employed composite nanolubricant in automotive air conditioning (AAC) system - Zawawi, N. M. M.; Azmi, W. H. (IOP Publishing, 2020)
Automotive Air conditioning (AAC) system is the contributor of harmful gasses emission and global warming. In order to solve the issues, investigation on potential improvement in lubrication used in air conditioning system is done to improve the system performance and efficiency. The performance of AAC system namely cooling capacity, compressor work, coefficient of performance (COP) and power consumption was investigated by comparing pure lubricant and Al2O3-SiO2/PAG nanolubricants. Performance of AAC by using different ranges of refrigerant charges (95 to 155 g) and speeds (1200 and 1800 rpm) was investigated. The result shows that the cooling capacity and COP of pure lubricant were relatively lower than Al2O3-SiO2/PAG nanolubricants. The compressor work and power consumptions of Al2O3-SiO2/PAG nanolubricants were greatly reduced. Cooling capacity and COP are enhanced by 102.99% and 23% respectively. The compressor work and power consumption are reduced by 25.9% and 28.24% respectively. From the results, nanolubricants gives more advantages in AAC performance over pure lubricant. Therefore, Al2O3-SiO2/PAG composite nanolubricants is recommended to be used as the compressor lubrication to enhance AAC performances system.